The effect of a.c. and d.c. electric ﬁeld on the dielectric properties of Na₀.₅Bi₀.₅TiO₃ ceramic - Suchanicz, J. (Condensed Matter Physics, 1999)
The dielectric properties were studied for Na₀.₅Bi₀.₅TiO₃ ceramic as a function of a.c. electric ﬁeld, d.c. electric ﬁeld, frequency, and temperature. The
increasing strength of a.c. electric ﬁeld shifts the electric permittivity function towards lower temperatures. However, d.c. electric ﬁeld reduces electric permittivity and slightly suppresses the frequency dispersion. These
effects can be connected with the existence in NBT of polar regions. Досліджено діелектричні властивості кераміки Na₀.₅Bi₀.₅TiO₃ як функції змінного і постійного електричного поля та температури. Збільшення змінного електричного поля зсуває діелектричну проникність
в область нижчих температур, а постійне електричне поле зменшує
проникність і дещо придушує її частотну дисперсію. Ці ефекти можуть бути пов’язані з існуванням в НВТ полярних областей.